How Does AI Enable Personalized Drug Dosing? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2017)
The era of one-size-fits-all medicine is gradually giving way to a more precise and individualized approach to healthcare. Personalized medicine, which tailo...
Keywords: Drug Discovery and Pharmaceutical AI; Enable; Personalized; Dosing; Artificial Intelligence; Machine Learning; Deep Learning